Histomorphological study of duodenum with special reference to RUT (Rapid Urease Test) negative dyspepsia in a rural care setting - Dr. Priyaranjan Chattopadhyay; Dr Pamela Nayak; Dr. Bijan Basak (Tropical Journal of Pathology and Microbiology, 2019)
Introduction:In our institute duodenal biopsies are taken in patients having either, unexplained anemia, weight loss, recurrent loose stool, abdominal pain, dyspepsia or suspected malabsorption. In the present study we have evaluated histomorphological features of duodenal biopsies in patients presented with specifically Rapid Urease Test (RUT) negative dyspepsia. Materials and Methods: A retrospective observational study was conducted and data of duodenal biopsies were collected from January 2017 to December 2018. Histopathology slides of duodenal biopsies were reevaluated. We have correlated clinical and endoscopic findings with various histomorphological parameters. Results: We have included total 99 cases. Demographic profile of our study population shows wide age range (9 years to 74 years) with mean age 39.8 years and Male: Female ratio 1.1:1. Dyspepsia was the common presenting symptoms (64.6% cases) and malabsorption was suspected in 29 cases. 28.3% cases show villous architectural abnormalities which correlate significantly with endoscopic findings of duodenal nodularity. Moderate to severe lamina propria lympho-plasmacytic infiltration seen in 58.56% cases and correlates significantly with dyspeptic symptoms. Duodenal biopsy was diagnostic in 3% cases. Conclusion: Diagnostic yield of duodenal biopsy is low but informative with proper clinical background.